Injection moulding parameters and performance of rice husk-high density polyethylene composite - Mat Isa, Naurah (2006)
A column end cap part was produced from a two stages process. The first stage was the compounding of rice husk and HDPE into pellet size and the second stage was moulding it into a product. Four sizes of rice husk were used at various compositions. The size ranged from 500 µm and below (coded as A, B, C and D) while the content of rice husk as the filler in the composite varies from 30, 40, and 50 percent of weight. A fixed amount of compatibilizer and lubricant were used. From the various compositions, only one formulation was selected for further analysis, based on the injection moulding processability and the strength of the material. The melt flow rate above 4 g/10 min was used to be the lower limit for injection moulding process. The best impact strength was the priority in the composite selection. A composite at 30 weight percent rice husk size A (RH30PEA) was found to have optimum rheological properties with respect to strength, thus used in the injection moulding process. An optimum condition was determined for the processing parameters involve melt temperature (180 ºC), injection pressure (60 kg/cm2), screw speed (240 rpm), screw backpressure (15 kg/cm2), holding time (6 sec), cooling time (42 sec) and mould temperature (30 ºC) using the Taguchi Method. The dimension of column end cap was taken as the quality measurement in the determination. The performance of the column end cap product was evaluated after the exposure to environment, accelerated UV aging and water. The impact strength experienced gradual drop with the time of exposure to environment, UV aging and water but not significantly affect the performance of the column end cap. The product absorbed less percentage of water compared to the conventional wood. The properties exhibited by the column end cap showed the advantage of using RHPE composite in the construction industry.